Organizational Commitment and Administrative Management in Public Service Delivery: Evidence from an Emerging Governance Context - Fabricio Miguel Moreno-Menéndez; Uldarico Inocencio Aguado-Riveros; Mohamed Mehdi Hadi-Mohamed; Ruben Darío Tapia-Silguera; Manuel Silva-Infantes; José Francisco Vía y Rada-Vittes; Luis Ángel Huaynate-Espejo; Vicente González-Prida (Administrative Sciences, 2025)
This study examines the relationship between organizational commitment and administrative management within a public service institution operating in an emerging governance context. Grounded in the three-component model of organizational commitment (affective, continuance, and normative) and classical administrative theory (planning, organizing, directing, and controlling), the research investigates how internal psychological bonds among frontline personnel influence institutional performance. A quantitative, cross-sectional, non-experimental design was applied, surveying 30 operational police officers using validated Likert-scale instruments. The results reveal a strong and statistically significant positive correlation between organizational commitment and administrative management (Spearman’s ρ = 0.775, p < 0.01), with normative commitment displaying the highest effect size (ρ = 0.812). These findings underscore the critical role of ethical obligation, loyalty, and affective alignment in enhancing managerial coherence and institutional responsiveness. The study contributes to ongoing debates on public sector reform and strategic human capital management by emphasizing the need for emotionally engaged and ethically anchored personnel. It aligns with Sustainable Development Goals (SDGs) 16 (Peace, Justice, and Strong Institutions) and 8 (Decent Work and Economic Growth), promoting inclusive, accountable governance and resilient administrative practices in resource-constrained environments.